Tantangan Dan Peluang Dalam Memadukan Etika Bisnis Dengan Budaya Organisasi - Putri, Alga Afrinda Shandilla (Multidisciplinary Journal of Religion and Social Sciences, 2025)
The purpose of this study is to analyze the challenges and opportunities faced by companies in integrating business ethics with organizational culture, and how the two influence each other in forming a productive and sustainable work environment. This study uses a literature study method by reviewing various relevant reference sources to explore the understanding of the relationship between business ethics and organizational culture, and its implementation in the context of modern companies. The results of the study indicate that although there are challenges in aligning business ethics values ​​with organizational culture, especially in dealing with differences in views and interests between individuals or groups, great opportunities arise if these two aspects can be applied harmoniously. Companies that are able to integrate business ethics with a strong organizational culture tend to have a higher level of trust from external and internal parties, and create a more stable and innovative work environment. This study also found that companies that are successful in overcoming these challenges can achieve sustainable competitive advantage